Pelatihan Aplikasi Learning Tools untuk Peningkatan Kualitas Pembelajaran Hybrid di Sekolah Dasar - Hendratno, Hendratno; Yermiandhoko, Yoyok; Wiryanto, Wiryanto; Subrata, Heru; Istiq'faroh, Nurul; Kantina, Sri (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
Teachers must master information and communication technology (ICT) because the lack of it will cause them to fall behind, making the teaching profession challenging. The training activity focuses on three learning tools, namely word wall, peardeck, and storyline. The steps involved in this training include: (1) Providing initial understanding of the importance of learning tool applications, (2) giving examples of how to use learning tools in teaching, (3) practicing the utilization of learning tools, (4) providing mentoring and direct practice in the use of learning tools in teaching, and (5) distributing questionnaires about the training implementation to the participants. The training program provides many benefits, such as: (1) increasing the effectiveness of teaching, (2) optimizing students' learning experience, (3) improving teachers' digital competence and creativity, (4) helping to overcome obstacles in using technology for teaching, (5) ultimately improving student learning outcomes.